The Effect of Conjugated Linoleic Acids, Vitamin E and Their Com¬bination on Lipid Peroxidation in Active Rheumatoid Arthritis - N Aryaeian; M Djalali; F Shahram; A Djazayeri; MR Eshragian; N Nadery; F Fatehi; M Zarei; M Chamari (Tehran University of Medical Sciences, 2009)
Background: Reactive oxygen species (ROS) have important role in the etiology and pathogenesis of Rheumatoid Arthritis (RA). We investigated the effect of conjugated linoleic acids (CLAs) and vitamin E on lipid peroxidation. Methods: In a randomized, double-blind placebo, controlled, clinical trial 87 patients with active RA were enrolled. They were divided into 4 groups, received one of the following daily supplement for 3 months; 1- group C: 2.5gr CLA, that contained 2 gr 50:50 mix of cis 9-trans11 and trans 10-cis 12 CLAs, 2- group E: 400mg Vitamin E, 3- group CE: CLAs  plus vitamin E, 4- group P: placebo. After supplementation Glutathione peroxidase (GSH-Px) level increased in C, E and CE groups, CE group had  lower GSH-Px than P group(P≤ 0.05). Results: Glutathione reductase (GR) increased in CE, C and P groups. Catalase increased in all groups, but enhancement was significant in C and CE. Superoxide dismutase (SOD) decreased in E and C (P≤ 0.05). Catalase and SOD did not show significant differences between groups. Malondialdehyde (MDA) decreased significantly in all groups but this decrease was only significant in CE in comparison with other groups. Conclusion:  CLAs might be useful in reducing oxidative stress in RA